1991
DOI: 10.1016/0042-6989(91)90048-a
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of eye growth and refractive state: An experimental study of emmetropization

Abstract: Abstract-During growth the vertebrate eye achieves a close match between the power of its optics and its axial length with the result that images are focused on the retina without accommodative effort (emmetropia). The possibility that vision is required for the regulation of eye growth was studied experimentally in chicks made myopic or hyperopic by different visual manipulations. After discontinuing these visual manipulations, the eyes returned quickly to emmetropia mainly by adjusting the growth of their vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
139
0
3

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(149 citation statements)
references
References 29 publications
5
139
0
3
Order By: Relevance
“…Within 7 days, they reach near emmetropia (the image is focused on the retina); however, rearing chickens in the dark retain hyperopia [Troilo and Wallman, 1991]. Troilo and Wallman [1991], as well as Schaeffel and Wagner [1996], have shown that retinal feedback is needed for controlled eye development to achieve emmetropia. While domestic chickens are precocial, American kestrels and barn owls are semi-altricial.…”
Section: Ocular Development In a Burrow-nesting Birdmentioning
confidence: 99%
“…Within 7 days, they reach near emmetropia (the image is focused on the retina); however, rearing chickens in the dark retain hyperopia [Troilo and Wallman, 1991]. Troilo and Wallman [1991], as well as Schaeffel and Wagner [1996], have shown that retinal feedback is needed for controlled eye development to achieve emmetropia. While domestic chickens are precocial, American kestrels and barn owls are semi-altricial.…”
Section: Ocular Development In a Burrow-nesting Birdmentioning
confidence: 99%
“…However, there is some evidence that optical correction can result in persistence of an error that might otherwise have naturally resolved or reduced. Emmetropisation appears to be partly reliant on normal visual experience and can be manipulated by optical correction (Dobson 1986;Hung 1995;Ingram 1991;Medina 1987;Troilo 1991). This raises the possibility that full refractive correction may not always be appropriate.…”
Section: Refractive Surgerymentioning
confidence: 99%
“…[1][2][3][4][5] However, if a decision on a prescription is made, it also introduces the tendency to place undue weight on with the wearing of spectacles in the face of deferring the development of emmetropization. [6][7][8][9][10][11][12][13][14][15][16][17] This concern raises a question that is yet to be answered: do hyperopic children really need the provision of full plus refractive error correction to meet these objectives?…”
Section: Introductionmentioning
confidence: 99%